2017
DOI: 10.1080/00498254.2016.1257835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferulic acid on the brain pharmacokinetics of tetramethylpyrazine in conscious rats

Abstract: 1. In traditional Chinese medicine, Angelica sinensis is often coprescribed with Ligusticum chuanxiong Hort for the treatment of ischemic cerebrovascular diseases. Tetramethylpyrazine (TMP) is one of the most important active ingredients isolated from Ligusticum chuanxiong Hort; ferulic acid (FA) is the main water-soluble component of Angelica sinensis. 2. The purpose of this study is to investigate the possible effect of FA on the brain pharmacokinetics of TMP in conscious Sprague-Dawley rats. The pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The results showed that TMP could easily pass though the BBB after intragastric administration, which is in accordance with our previous study (Wu et al, ). The results also revealed that the maximum concentration ( C max ) of TMP in brain was improved dramatically after co‐administration of BO (15 and 30 mg/kg, i.g.…”
Section: Resultssupporting
confidence: 93%
“…The results showed that TMP could easily pass though the BBB after intragastric administration, which is in accordance with our previous study (Wu et al, ). The results also revealed that the maximum concentration ( C max ) of TMP in brain was improved dramatically after co‐administration of BO (15 and 30 mg/kg, i.g.…”
Section: Resultssupporting
confidence: 93%